A novel hapten and monoclonal antibody-based indirect competitive ELISA for simultaneous analysis of alternariol and alternariol monomethyl ether in wheat. (December 2018) - Wang, Jianyi; Peng, Tao; Zhang, Xiya; Yao, Kai; Ke, Yuebin; Shao, Bing; Wang, Zhanhui; Shen, Jianzhong; Jiang, Haiyang
Abstract: This study synthesized a new alternariol (AOH) hapten. The AOH had an alkylation reaction with ethyl 4-bromobutyrate, followed by hydrolysis and purification, and then conjugated with keyhole limpet hemocyanin to immunize mice and successfully produced two kinds of monoclonal antibodies (mAbs), namely the antibodies which can recognize both AOH and alternariol monomethyl ether (AME) and the ones that can specifically recognize AOH. Wherein, mAb 13D8 can uniformly recognize AOH and AME with the 50% inhibition concentration (IC50 ) values of 9.4 ng/mL and 9.7 ng/mL, respectively. An indirect competitive ELISA (icELISA) was established by mAb 13D8 to simultaneously detect AOH and AME, with the limit of detection (LOD) being 0.7 ng/mL and 1.0 ng/mL, respectively. The average recoveries in spiked wheat sample were 84.5–107.6% with the coefficient of variation (CV) lower than 10%. The established icELISA method was used to detect 13 real samples with the same results as HPLC-MS/MS, indicating that the method is suitable for simultaneous detection of AOH and AME in wheat. Highlights: A new derivative of alternariol was synthesized and used as immunizing hapten. The obtained monoclonal antibody could uniformly recognize the mycotoxins alternariol and alternariol monomethyl ether. The effect of coating hapten on the sensitivity of ELISA was studied. The proposed ELISA could be used as a rapid screening method for co-analysis of alternariol and alternariol monomethyl ether.